Holistic Communication in Guidance and Counseling Services to Foster Students’ Discipline at SMP Negeri 4 Medan - Darmansyah Hasibuan (Yayasan Bayt Shufiya Nusantara, 2024)
This study aims to examine communication patterns in guidance and counseling services to students at SMP Negeri 4 Medan. This study used a mixed methods approach with primary data collection through interviews with teachers, students, and principals, as well as distributing questionnaires to students as quantitative data. The data were analyzed descriptively analytically by combining the interview results and questionnaire findings presented in tabular form. The results showed that the communication patterns applied by teachers in dealing with problem students have reflected a holistic approach that not only emphasizes corrective aspects, but also builds emotional, empathic, and educative relationships with students. This research confirms that holistic communication in guidance and counseling is a strategic approach that can be applied sustainably in creating a humanist and transformative educational climate in schools.